1998
DOI: 10.1097/00005537-199808000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment of headache after suboccipital acoustic tumor removal

Abstract: Headache is a significant problem with the suboccipital approach for acoustic tumor removal. The majority of patients that complain of headache can be adequately treated with nonsteroidal anti-inflammatory drugs (NSAIDs). If pain is unrelieved by NSAIDs, treatment becomes problematic. The authors' early experience with divalproex sodium/verapamil is encouraging and deserves further investigation as a treatment for these refractory cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 7 publications
2
30
0
3
Order By: Relevance
“…33 Finally, Hanson et al reported their experience managing pain after suboccipital VS resection, finding that approximately 13% of patients did not respond to simple analgesic therapy. 13 Within the small group of patients with refractory symptoms, divalproex sodium and verapamil provided significant relief in all cases.…”
Section: Headache Classification and Treatmentmentioning
confidence: 89%
“…33 Finally, Hanson et al reported their experience managing pain after suboccipital VS resection, finding that approximately 13% of patients did not respond to simple analgesic therapy. 13 Within the small group of patients with refractory symptoms, divalproex sodium and verapamil provided significant relief in all cases.…”
Section: Headache Classification and Treatmentmentioning
confidence: 89%
“…A post-craniotomy headache, which is severe and lasts longer than 6 months, has been found in 30 of 95 patients (32 %) who were operated on for acoustic neurinoma [57]. Its prevalence has been shown to depend on the time interval between surgery and survey with a decrease over time [58, 59]. For acoustic neuroma surgery, Schessel et al .…”
Section: Selected So-called ‘Secondary Headaches’mentioning
confidence: 99%
“…The presence of post-craniotomy headaches (PCH) often interfere with patients' quality of life (1)(2)(3)(4)(5) and constitute a challenge for those who deal with them (6). Only recently has scientific interest increased concerning this type of headache (7).…”
Section: Introductionmentioning
confidence: 99%